Right atrial volume index and right atrial volume predict atrial fibrillation recurrence: A meta-analysis. - Jia-Ming Han; Qian Xie; Xiu-Ying Song; Yu-Lan Ma (PLoS ONE)
Background Atrial volume index and atrial volume have recently been identified as predictors of atrial fibrillation (AF) recurrence following electrical cardioversion or radiofrequency ablation. However, most studies have reported the relationship between LAVI/LAV and AF recurrence, whereas there is little information on the relationship between RAVI/RAV and AF recurrence. Therefore, we performed a meta-analysis to assess the relationship between the risk of AF recurrence and RAVI/RAV in patients with AF who underwent electrical cardioversion or radiofrequency ablation. Methods CNKI, Wanfang Database, Pubmed, Embase, Cochrane Library, and Web of Science were searched up to October 01, 2024. A meta-analysis of relative risk data from prospective and retrospective cohort studies that reported on the relationship between the risk of AF recurrence and RAVI/RAV in patients with AF after electrical cardioversion or radiofrequency ablation was performed. Results The results showed that patients with AF recurrence had a higher mean right atrial volume index (RAVI) compared to patients with no recurrence. After electrical cardioversion or radiofrequency ablation, RAVI can independently predict the recurrence of AF (OR = 1.06, 95%CI (1.02, 1.11)). The average right atrial volume (RAV) of patients with AF recurrence was higher than that of patients without AF recurrence. After electrical cardioversion or radiofrequency ablation, RAV can independently predict the recurrence of AF (OR = 1.02, 95%CI (1.00, 1.05)). Conclusion Patients with AF recurrence after electrical cardioversion or radio frequency ablation had higher mean RAVI and RAV compared to patients with no recurrence. After electrical cardioversion or radiofrequency ablation in patients with AF, higher levels of RAVI and RAV increase the chance of recurrence of AF.